2003
DOI: 10.1161/01.cir.0000041045.26774.1c
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Ultrasonic Tissue Characterization (Backscatter) in the Evaluation of Left Ventricular Myocardial Structure and Mechanics in Essential Arterial Hypertension

Abstract: Background-Ultrasonic backscatter parameters were analyzed in hypertensive patients and divided into groups according to both severity of left ventricular hypertrophy (LVH) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…In recent studies, CVI reduction has been considered as an early indicator of contractile dysfunction before recognizing the geometric remodeling or the drop in fractional shortening, being attributed to the increase or disarray in the myocardial collagen network. 14,35 However, the downregulation and redistribution of Cx43 has been also found in the hypertrophied myocardium, 30 suggesting a possible role for the remodeling of gap junctions in the attenuated CVI. In this study, we reported the sequential alterations in contractile function and the expression and distribution of Cx43 in hearts of rabbits fed on cholesterol-enriched diet, that have normal myocardial architecture and ridding of transmural fibrosis, and also the reversal of these findings on withdrawal of the diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent studies, CVI reduction has been considered as an early indicator of contractile dysfunction before recognizing the geometric remodeling or the drop in fractional shortening, being attributed to the increase or disarray in the myocardial collagen network. 14,35 However, the downregulation and redistribution of Cx43 has been also found in the hypertrophied myocardium, 30 suggesting a possible role for the remodeling of gap junctions in the attenuated CVI. In this study, we reported the sequential alterations in contractile function and the expression and distribution of Cx43 in hearts of rabbits fed on cholesterol-enriched diet, that have normal myocardial architecture and ridding of transmural fibrosis, and also the reversal of these findings on withdrawal of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…The hypercholesterolemic rabbit hearts were also demonstrated to have systolic dysfunction in vivo, as measured using the CVI, mitral ring systolic velocity, and modified Tei index, all of which have been reported to be more sensitive than the fractional shortening. 14,22,29 These findings of hyperlipidemia-induced protein and contractile change raised an interesting question regarding the relationship between the alterations. Our findings suggest that in the hyperlipidemic rabbits, the remodeling of cardiomyocyte gap junctions may contribute to the impaired systolic function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with previous cardiovascular disease were excluded. patients with EH with comparable LVMI were selected to avoid the confounding effect of the increase of LVM on IBS measures, because an increase in IBS absolute values and a reduction of IBS cyclic variation (CV) has been described in patients with EH with markedly increased LVM (19). BP was measured by the same physician with a mercury sphygmomanometer.…”
Section: Methodsmentioning
confidence: 99%